Estudo genético – quantitativo do desempenho de ovinos da raça Santa Inês em exposições agropecuárias - Alves, Anderson Antônio Carvalho (2015)
The aim in this study was to evaluate the genetic nature of the ability of an animal to rank among the top three on age categories (HAB3) and its total score (PTO) on trial championships held in different agricultural fairs. Records belonging to the Brazilian Association of Santa Inês (ABSI) and related to fairs that occurred between the years 2012 and 2014 were used. We evaluated the HAB3 for animals between 4 and 36 months, divided into 16 categories according to their age, and the PTO, considering all individual championships performed during the agricultural fair, where the animals belonging until the 4th age category (4-8 months) competed in categories and in subsequent championships to define the Future Sheep Champion, and confirmed animals (over 8 months) competed for the top award of the Great Breed Champion. The final data files contained 3,180 placing records (HAB3) for 1,896 animals and 4,383 information on the obtained scores (PTO) for 2,170 animals. The pedigree file included 4,069 animals. Variance components were estimated fitting threshold and linear animal models for ABI3 and TS, respectively, by Bayesian analysis using the Gibbs sampler. The posterior means of heritability and repeatability were, respectively, 0.10 ± 0.07 and 0.57 ± 0.11 for HAB3 and 0.12 ± 0.04 and 0.31 ± 0.02 for PTO. Low heritability values reported for these traits reveal a strong influence of environment factors, such as the treatment offered to the animals. The repeatability values suggest high correlation between the animal classifications, implying that animals ranked in the top three in the categories of age, tend to have similar performance in subsequent competitions. However, for the total score, the observed performance has moderate confidence be repeated over time. We conclude that the selection and use of rams who achieved good performances in trial competitions feature no major guarantees that their offspring have the same capacity.